Analyzing the Use of Flouting Maxims in Deddy Corbuzier’s Podcast - Bening Artha Amartya; Afiifah Al Al Rosyiidah (Journal of Social, Culture, and Language, 2025)
This study aims to describe the types and strategies of flouting maxims in Deddy Corbuzier’s podcast. This study applies qualitative research method. The findings reveal that all four types of flouting maxims are present: maxim of quality is flouted 18 times, maxim of quantity appears 13 times, maxim of relevance is flouted 7 times, while the maxim of manner is flouted 2 times. Furthermore, eight distinct strategies for maxim flouting were identified. The strategy of providing too much information was the most frequent, occurring 12 times. Hyperbole was noted 8 times, while changing topics occurred 7 times. Other strategies included metaphor (6 instances), irony (2), banter (2), being obscure (2), and giving too little information (2). Keywords: Flouting maxim, type, strategies, Deddy Corbuzier’s podcast